2010
DOI: 10.3109/00016349.2010.518594
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies in newborns of women with type 1 diabetes: nationwide population‐based study in Norway, 1999–2004

Abstract: Women in Norway with type 1 diabetes experience a significantly higher risk of congenital anomalies in their babies compared with the background population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 25 publications
4
44
0
1
Order By: Relevance
“…Both animal and human studies have shown uncontrolled or poorly controlled maternal pregestational diabetes significantly increases the risk of offspring with major malformations [6,7]. Epidemiologic studies also have found a strong link between pregestational diabetes and birth defects [8,9].…”
Section: What Do We Know?mentioning
confidence: 98%
“…Both animal and human studies have shown uncontrolled or poorly controlled maternal pregestational diabetes significantly increases the risk of offspring with major malformations [6,7]. Epidemiologic studies also have found a strong link between pregestational diabetes and birth defects [8,9].…”
Section: What Do We Know?mentioning
confidence: 98%
“…Diabetes inhibits mRNA and protein expression of both small (SK3) and intermediate (IK) conductance calcium-activated potassium channels in the cavernous tissue of diabetic rats, which could play a key role in the development of erectile dysfunction in diabetic rats (Zhu et al 2010). There are several reports in the literature that babies born to type I diabetic mothers are having altered growth and body composition, skeletal deformities as well as other abnormalities (Mughal et al 2010;Eidem et al 2010). Generation of oxidative stress in the hyperglycemic condition can result in reproductive dysfunction in experimental diabetic models (Agarwal and Said 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Despite substantial advances in the treatment of type 1 diabetes over recent decades and focus on the necessity of good care before and during pregnancy for women with the disease, most research studies indicate that women with pregestational type 1 diabetes still have a considerably higher risk of pregnancy complications and adverse pregnancy outcome compared with the background population [1][2][3][4][5][6]. The risk of stillbirth or perinatal death has, according to recent studies, varied between three and six times the risk in women without diabetes [7].…”
Section: Introductionmentioning
confidence: 99%